2019
DOI: 10.1063/1.5091108
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of ultrasound heating for the correction of viscous heating artifacts in soft tissue temperature measurements

Abstract: Measuring temperature during focused ultrasound (FUS) procedures is critical for characterization, calibration, and monitoring to ultimately ensure safety and efficacy. Despite the low cost and the high spatial and temporal resolutions of temperature measurements using thermocouples, the viscous heating (VH) artifact at the thermocouple-tissue interface requires reading corrections for correct thermometric analysis. In this study, a simulation pipeline is proposed to correct the VH artifact arising from temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 35 publications
(45 reference statements)
1
8
0
Order By: Relevance
“…The artifact contribution decreased with the pressure amplitude and FUS beam location. These results corroborate previous studies that suggested placing the thermocouple tip slightly off the FUS focal spot to reduce the artifact [15], [19], [34]. This is a feasible approach, but a correction of the temperature decay with the beam profile is necessary to correctly retrieve the temperature estimation at the focal spot.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The artifact contribution decreased with the pressure amplitude and FUS beam location. These results corroborate previous studies that suggested placing the thermocouple tip slightly off the FUS focal spot to reduce the artifact [15], [19], [34]. This is a feasible approach, but a correction of the temperature decay with the beam profile is necessary to correctly retrieve the temperature estimation at the focal spot.…”
Section: Discussionsupporting
confidence: 90%
“…However, the method is limited for the analysis of the cooling time only. An analysis of the heating pattern would require simulations of heating due to both ultrasound absorption and viscous heating effect, as we presented in a recent work [19]. However, simulations require the estimation of the viscous heating contribution in different experimental conditions which, as we demonstrate here, is highly variable with acoustic parameters and thermocouple type.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…A sharp 3-dB temperature decrease occurred at 0.4 mm away from the center of the focus laterally and 1.6 mm in depth. The temperature returned to baseline within 2 seconds after 1 ms stimulations [37], [38].…”
Section: K Safety Assessment Of Fus Parametersmentioning
confidence: 93%
“…The simulation model is shown in Fig.5, with the tissue material properties listed in TABLEI. The only change is the acoustic absorption coefficient š›¼ '6 which was measured by comparing the relative amplitude of ultrasound through transmission measurements in the tissue sample and in free water[26]. For this measurement, a 1 MHz transducer with a diameter of 20 mm was used as a transmitter and a hydrophone (HNR 0500, Onda Corporation, California, USA) was used as a receiver.…”
mentioning
confidence: 99%